2020
DOI: 10.3390/f11090980
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Tree Decay Duration on Mechanical Stability of Norway Spruce Wood (Picea abies (L.) Karst.)

Abstract: Wood properties have an influence on the safety around the tree itself as well as on actual possibilities of using wood. The article focuses on the wood properties of the Norway spruce (Picea abies (L.) Karst.) in reference to the time since the tree has decayed. The study was conducted among mature tree stands of spruce in Białowieża Forest, where over the last 10 years there has been a weakening of spruce tree stands due to water deficiency which has contributed to the gradation of the European spruce bark b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…If white rot and brown rot fungi cause a wood mass loss, as the wood density decreases, so do its mechanical properties [45]. This effect was shown in research [21], where the mechanical properties gradually decreased with increasing duration of degradation processes due to fungi. However, Kržišnik et al [22] in their research compared only the effect of blue-stained wood on its properties; the differences in the density of control and blue-stained samples were not statistically significant.…”
Section: Mechanical Properties Of Wood From Beetle-attacked Treesmentioning
confidence: 89%
See 4 more Smart Citations
“…If white rot and brown rot fungi cause a wood mass loss, as the wood density decreases, so do its mechanical properties [45]. This effect was shown in research [21], where the mechanical properties gradually decreased with increasing duration of degradation processes due to fungi. However, Kržišnik et al [22] in their research compared only the effect of blue-stained wood on its properties; the differences in the density of control and blue-stained samples were not statistically significant.…”
Section: Mechanical Properties Of Wood From Beetle-attacked Treesmentioning
confidence: 89%
“…In the case of the mechanical properties of bark beetle-infested wood, changes in these properties over a longer time horizon (i.e., over a period of several years) may be caused by the action of fungi. In their study, Jelonek et al [21] dealt with changes in the mechanical properties of bark beetle-infested Norway spruce wood after the beetles had left the stump for several years. Research has shown a declining trend in average values of modulus of rupture (MOR), as well as modulus of elasticity (MOE).…”
Section: Mechanical Properties Of Wood From Beetle-attacked Treesmentioning
confidence: 99%
See 3 more Smart Citations